Sex-Specific Treatment Effects After Primary Percutaneous Intervention: A Study on Coronary Blood Flow and Delay to Hospital Presentation - Cenko, Edina; van der Schaar, Mihaela; Yoon, Jinsung; Kedev Sasko; Valvukis, Marija; Vasiljevic, Zorana; Ašanin, Milika; Miličić, Davor; Manfrini, Olivia; Badimon, Lina; Bugiardini, Raffaele (My University, 2019)
Background We hypothesized that female sex is a treatment effect modifier of blood flow and related 30-day mortality after primary percutaneous coronary intervention ( PCI ) for ST -segment-elevation myocardial infarction and that the magnitude of the effect on outcomes differs depending on delay to hospital presentation. Methods and Results We identified 2596 patients enrolled in the ISACS - TC (International Survey of Acute Coronary Syndromes in Transitional Countries) registry from 2010 to 2016. Primary outcome was the occurrence of 30-day mortality. Key secondary outcome was the rate of suboptimal post- PCI Thrombolysis in Myocardial Infarction ( TIMI ; flow grade 0-2). Multivariate logistic regression and inverse probability of treatment weighted models were adjusted for baseline clinical covariates. We characterized patient outcomes associated with a delay from symptom onset to hospital presentation of ≤120 minutes. In multivariable regression models, female sex was associated with postprocedural TIMI flow grade 0 to 2 (odds ratio [ OR ], 1.68; 95% CI , 1.15-2.44) and higher mortality ( OR, 1.72; 95% CI , 1.02-2.90). Using inverse probability of treatment weighting, 30-day mortality was higher in women compared with men (4.8% versus 2.5%; OR , 2.00; 95% CI , 1.27-3.15). Likewise, we found a significant sex difference in post- PCI TIMI flow grade 0 to 2 (8.8% versus 5.0%; OR , 1.83; 95% CI , 1.31-2.56). The sex gap in mortality was no longer significant for patients having hospital presentation of ≤120 minutes ( OR , 1.28; 95% CI , 0.35-4.69). Sex difference in post- PCI TIMI flow grade was consistent regardless of time to hospital presentation. Conclusions Delay to hospital presentation and suboptimal post- PCI TIMI flow grade are variables independently associated with excess mortality in women, suggesting complementary mechanisms of reduced survival. Clinical Trial Registration URL : http://www.clinicaltrials.gov . Unique identifier: NCT 01218776.